The effectiveness of giving ST 36 Acupressure and Deep Breathing Relaxation on the level of maternal pain during the first stage of the Active Phase at the Duren Sawit District Health Center, East Jakarta in 2022 - Ipah Farida; Resi Galaupa; Ipah Farida (East Asian Journal of Multidisciplinary Research, 2022)
The presence of labor pain can cause a lack of endorphins which will cause discomfort, anxiety and excessive stress which will hinder the course of labor. This study aims to determine the effect of giving ST 36 Acupressure Techniques and Deep Breathing Relaxation on maternal pain levels during Active Phase I. The design in this study used a Quasy Experiment with a personal pre and post test design, the samples taken in this study were 25 respondents. The instruments used were the VAS Pain Scale (Visual Analouge Scale) and the Observation Sheet. From the results of Univariart data testing, it was found that 96% of the age distribution were in the age group of 20-35 years, with the last education being high school with a percentage of 52%. the mother gave birth to the first stage of the active phase with a p-value of 0.000.